Pedagogy of Transgression in Preschool Education - Stanisława Włoch (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The 21st century is characterized by the accelerating pace of life as well as civilization, cultural and technological changes. Therefore, it requires a new view on the future human being. Education from preschool to adulthood plays a crucial role in this regard. Contemporary preschool pedagogy is searching for innovative solutions in the field of unleashing genetic potential and development of the multidimensional personality. One of the new ideas is pedagogy of transgression, consisting in exceeding one's own limitations through activity, experience, self-reliance and responsibility. The paper shows theoretical foundations of transgression, factors which unleash child's capabilities, organization of the educational field as well as organization of the process of transgression-based development.